I cortocircuiti dell’accoglienza. Note critiche su retoriche, politiche e sfruttamento delle migranti nei mercati del sesso - Abbatecola, Emanuela; Popolla, Mariella (SocietàMutamentoPolitica, 2020)
Reflecting on the quality of the reception paths dedicated to migrant people always implies an effort aimed at keeping different dimensions together and giving account of their complexity. This is because the prevailing cultural models generate processes defining the reality which in turn shape priorities and interventions, often contributing to cause short circuits between migration policies, mobility strategies and the effectiveness of reception. This contribution aims to shed light on some of these “short circuits” at the origin of the current critical issues of the pathways of social protection of migrants exploited in the sex markets. These reflections will be inspired by the rich material of two field researches.